2019
DOI: 10.1055/a-0862-0263
|View full text |Cite
|
Sign up to set email alerts
|

Histologic assessment of the intestinal wall following duodenal mucosal resurfacing (DMR): a new procedure for the treatment of insulin-resistant metabolic disease

Abstract: Background and study aims Minimally invasive procedures that replicate aspects of bariatric surgery with more favorable safety and tolerability offer an attractive alternative in management of metabolic disease. Duodenal mucosal resurfacing (DMR), an endoscopic procedure using hydrothermal ablation, is designed to remove surface epithelium to allow subsequent epithelial regeneration and a reset to a more insulin-sensitive state. Materials and methods DMR was performed on a healthy pig under general a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Duodenal mucosal resurfacing (DMR) is a minimally invasive endoscopic procedure performing circumferential mucosal lift and hydrothermal ablation of the duodenal mucosa. 15 The first-in-human safety trial showed that DMR is safe and able to improve glycaemic control in proportion to the length of the ablated duodenal mucosal segment. 16 17 The following multicentre, open-label REVITA-1 trial in 46 patients with poorly controlled T2D showed a significant reduction of baseline HbA1c at 24 weeks after DMR of −10±2 mmol/mol (−0.9%±0.2%; p<0.001).…”
Section: Introductionmentioning
confidence: 99%
“…Duodenal mucosal resurfacing (DMR) is a minimally invasive endoscopic procedure performing circumferential mucosal lift and hydrothermal ablation of the duodenal mucosa. 15 The first-in-human safety trial showed that DMR is safe and able to improve glycaemic control in proportion to the length of the ablated duodenal mucosal segment. 16 17 The following multicentre, open-label REVITA-1 trial in 46 patients with poorly controlled T2D showed a significant reduction of baseline HbA1c at 24 weeks after DMR of −10±2 mmol/mol (−0.9%±0.2%; p<0.001).…”
Section: Introductionmentioning
confidence: 99%
“…An additional study by de Moura et al performed histologic assessment of porcine duodenal epithelium following treatment with the Revita procedure [54]. These findings confirmed that mucosa resurfacing promotes superficial mucosal ablation of the villus tips to the crypt base while also observing that the submucosal lift creates a submucosal barrier protection against deeper tissue injury.…”
Section: Duodenal Mucosal Resurfacingmentioning
confidence: 80%
“…The duodenal mucosa is separated from the submucosal layers by injecting normal saline, followed by circumferential hypothermal ablation of the mucosal layer. 99 A direct relationship was observed between the length of the ablated duodenal segment and the improvement in metabolic profile. 100 To further study the efficacy of DMR, de Oliveira et al 101 conducted a meta-analysis embracing various metabolic variables (HbA1C, fasting plasma glucose, weight loss, liver enzymes, and hepatic steatosis).…”
Section: Management Of Obesity In Patients With Nafldmentioning
confidence: 90%